The Role Of The Manpower Office in Preventing Illegal Labor in Sampang Regency - Mohammad Hori; Sri Roekminiati; Ika Devy Pramudiana; Sapto Pramono (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This research is a descriptive qualitative research, data collection techniques using interviews, observations, and documentation. The purpose of the study is to describe the role of the Manpower Office in the prevention of Manpower and to find out what obstacles are experienced by the Manpower Office in the context of preventing Illegal Labor in Sampang Regency. The research informant is the Head of the Office, Head of Placement and Expansion of TKI of the Sampang Regency Manpower and Transmigration Office. Data analysis uses an interactive model. The results of the study show that the Sampang Regency Government Manpower Office has a role as a regulator carried out through the provision of socialization and counseling to the community, providing supervision for normative issues to be handled. The role as a mediator is carried out by collecting data on prospective migrant workers who register themselves. The role as a facilitator is to respond to incoming reports and will later be handled according to existing procedures and regulations. The obstacles of the Manpower and Transmigration Office in the context of preventing Illegal Labor in Sampang Regency consist of Internal Obstacles related to the instability of this system as evidenced by the dual functions of BNP2TKI. Weak coordination between government agencies in charge of managing migrant workers. Weak supervision of PJTKI whose operational permits have expired. External obstacles include background, educational factors, knowledge/experience, condition of prospective kindergartens, low quality of human resources from prospective migrant workers